Do local or global macroeconomics variables explain the cumulative Colombian stock exchange index in dollars? - Espitia-Murcia, Felipe E. (2020)
This research studies the link between local and global macroeconomic variables within the cumulative Colombian exchange stock index (COLCAP) returns in dollars. The local variables selected were the exchange rate, the consumer price index, industrial production, and the central bank rate. On the other hand, the global macroeconomics variables were the Brent oil price, the SP 500 index, the VIX index, and the 3-month treasury rate, as a proxy of the FED rate. The sample selected is from August 2002 to December 2019. This paper investigates how could be the relationship with two different methodologies. Contemporaneously using an OLS estimation, and dynamic using a VAR model. Additionally, a parametric causal test (Granger test), and non-parametric causal test (Pesaran and Timmermann test) were used to understand if the variables selected has a unidirectional or bidirectional causal relation. For local variables, the exchange rate and the consumer price index showed to be relevant to explain the COLCAP returns but differ in the estimation methodology. MSCI Emerging market index displayed to be significant on both methodologies, like a global variable. These results may be considered from the investor and the policymaker perspective on the decision-making process.